The effect of entrepreneurial ecosystems on entrepreneurship in Portugal:the difference between dreaming a startup and actually starting it - Gaspar, Fernando (2019)
Entrepreneurship’s importance has been frequently highlighted in the literature and five reasons have been mostly pointed out: it contributes to the creation of job, it contributes to innovation, it increases the creation of wealth, it contributes to the development of the economy and of the society and, finally, it constitutes a more and more important career option for a good part of the workforce (F.C. Gaspar, 2009). This work analyses the variation in start-up creation across the Portuguese NUT3 regions, using data available from two different sources. In the period 2014-2017, the birth of startups is measured through notary acts of new company creation and activity start is measured through the first submission of salaries lists to ministério do trabalho e solidariedade social (MTSS). This data is analyzed with other social and economic variables trying to determine environmental factors that help explain the large differences between the regions. Particular attention is focused on measuring the birth and the activity of the so called “entrepreneurial ecosystems”, as defined in the literature (Alvedalen & Boschma, 2017; Boutillier, Carré, & Levratto, 2016; Kuckertz, 2019). In face of the low levels of entrepreneurship that most Portuguese NUT3 regions show, recommendations are made for economic policies that may increase entrepreneurial activity. The results also show that the demand derived factors assume an enormous weight in the explanation of the differences between the districts, which must inspire eventual actions of the local entities. New policies are needed to further entrepreneurial activity in the interior regions and the islands.